Quantitative Magnetization EXchange MRI Measurement of Liver Fibrosis Model in Rodents. Issue 1 (6th May 2022) - Wilczynski, Ella; Sasson, Efrat; Eliav, Uzi; Navon, Gil; Nevo, Uri
Abstract : Background: Quantitative MRI can elucidate the complex microstructural changes in liver disease. The Magnetization EXchange (MEX) method estimates macromolecular fraction, such as collagen, and can potentially aid in this task. Hypothesis: MEX sequence, and its derived quantitative macromolecular fraction, should correlate with collagen deposition in rodents liver fibrosis model. Study Type: Prospective. Animal Model: Sixteen adults Sprague–Dawley rats and 13 adults C57BL/6 strain mice given carbon tetrachloride (CCl4 ) twice weekly for 6 or 8 weeks. Field Strength/Sequence: A 7 T scanner. MEX sequence (selective suppression and magnetization exchange), spin‐echo and gradient‐echo scans. Assessment: Macromolecular fraction ( F ) and T1 were extracted for each voxel and for livers' regions of interest, additional to calculating the percentage of F > 0.1 pixels in F maps (high‐ F ). Histology included staining with hematoxylin and eosin, picrosirius red and Masson trichrome, and inflammation scoring. Quantitative collagen percentage calculated using automatic spectral‐segmentation of the staining. Statistical Tests: Comparing CCl4 ‐treated groups and controls using Welch's t‐test and paired t‐test between different time points. Pearson's correlation used between ROI MEX parameters or high‐ F fraction, and quantitative histology. F or T1, and inflammation scores were tested with one‐sided t‐test. P < 0.05 was deemed significant. Results: Rats: F values were significantly different after 6 weeks of treatment (0.10 ± 0.02) compared to controls (0.080 ± 0.003). After 8 weeks, F significantly increased (0.11 ± 0.02) in treated animals, while controls are not significant (0.0814 ± 0.0008, P = 0.079). F correlated with quantitative histology ( R = 0.87), and T1 was significantly different between inflammation scores (1: 1332 ± 224 msec, 2: 2007 ± 464 msec). Mice: F was significantly higher (0.062 ± 0.006) in treatment group compared to controls (0.042 ± 0.006). F and high‐ F fraction correlated with quantitative histology ( R = 0.88; R = 0.84). T1 was significantly different between inflammation scores (1:1366 ± 99 msec; 2:1648 ± 45 msec). Data Conclusion: MEX extracted parameters are sensitive to collagen deposition and inflammation and are correlated with histology results of mouse and rat liver fibrosis model. Evidence Level: 1 Technical Efficacy: Stage 3